Concentration of nitric oxide oxidation products and antioxidant vitamins in chicken fed with supplemental zinc - Semiha Dede; Yeter Değer; Tahir Kahraman; Nurcan Dönmez (Eurasian Journal of Veterinary Sciences)
The aim o! this study ts to determine o! the effect of supplemental zinc on the concentration of the oxidation products of nilnc oxide and antioxidant vitamins in chicken serum. Chicken were divided into three experimental groups and one control group, each group containing seven chicken. The experimental groups were treated supplement zinc (125, 500, 1000 ppm). The concentration of nitric oxide oxidation products and antioxidant vitamins in the serum of zinc treated chicken were analysed with spectrophotometry ally. Nitrate (ppm), nitrite (ppm), vitamin E (mg/dl), vitamin C (mg/dl) concentrations ol experimental groups 1.. 2., 3. and control group were found : 6.16, 6.41, 13.16, 7.38, 1.09, 1.20, 1,30, 1.78; 0.121, 0,326, 0.247. 0,313: 0.927, 1.682. 1.204, 1.323 respectively. Nitrite levels of control groups was found higher than experimental groups l.and 2 (p<0.05). Nitrate levels were not significantly diflerentes between groups. The vitamin E concentration of 1 experimental group was lower than other groups (p<0.05). The vilamin C concentration of 2 experimental group was higher than 1 and 3 experimental groups (p<0.05). In conclusion; the concentration of nitric oxide oxidation products in serum of zinc treated chicken were not differentes between groups, but the antioxidant vitamins levels were increased. These results support the idea that zinc has an important rol in the metabolism as an antioxidant trace element in chicken.